The impact of servant leadership on organisational commitment among the highly talented: the role of challenging work conditions and psychological empowerment. (1st January 2011) - Asag-Gau, Lamia; van Dierendonck, Dirk
In this research, the authors tested a model in which the challenging work conditions of employees at work and empowerment mediated the influence of servant leadership on organisational commitment. The main aim was to provide additional insight into the relevance of leadership for talent management. In a sample of 174 highly talented employees, challenging work conditions and empowerment mediated the relationship of servant leadership to organisational commitment. The results indicated that the conceptual model tested with a structured equation modelling had an excellent fit. Servant leadership was positively related to challenging work conditions. Following challenging work conditions were related to three out of four psychological empowerment dimensions. Striking is that the empowerment dimension of servant leadership explained additional variance in the meaning aspect of psychological empowerment and that meaning was the most important dimension in relation to organisational commitment.